U.S. College Students' Sexual Activity: The Unique and Interactive Effects of Emotion Regulation Difficulties and Attachment Style. Issue 1 (2nd January 2016) - Stroud, Catherine B.; Hershenberg, Rachel; Cardenas, Stephanie; Greiter, Elizabeth; Richmond, Margaret
ABSTACT: Objectives: This study explored the association between emotion regulation difficulties and sexual activity, and whether emotion regulation difficulties moderated the link between attachment and sexual activity. Methods: U.S. college students (N = 373) from two institutions completed self-report measures of sexual activity, emotion regulation difficulties and attachment. Results: Findings indicated that greater emotion regulation difficulties were associated with less frequent exclusive sexual activity. Moreover, emotion regulation difficulties moderated links between attachment avoidance and sexual activity, and associations varied according to relational context and gender. Conclusions: Implications for promoting sexual health and relationship intimacy are discussed.